Reply to Zandi, M.; Soltani, S. Comment on "Alfassam et al. Development of a Colorimetric Tool for SARS-CoV-2 and Other Respiratory Viruses Detection Using Sialic Acid Fabricated Gold Nanoparticles. Pharmaceutics 2021, 13, 502" - Haya A. Alfassam; Majed S. Nassar; Manal M. Almusaynid; Bashayer A. Khalifah; Abdullah S. Alshahrani; Fahad A. Almughem; Abdullah A. Alshehri; Majed O. Alawad; Salam Massadeh; Manal Alaamery; Ibrahim M. Aldeailej; Aref A. Alamri; et al. (MDPI AG, 2022)
When COVID-19 was first announced back in 2019, there were vast number of attempts to halt the progression of the SARS-CoV-2 virus once and for all [...]